Outcomes of Noninvasively Treated Idiopathic Toe Walkers. Issue 1 (February 2019) - Radtke, Kerstin; Karch, Nataliia; Goede, Fabian; Vaske, Bernhard; von Lewinski, Gabriela; Noll, Yvonne; Thren, Anneke
Idiopathic toe walking (ITW) causes a common problem in pediatric orthopaedics. In the literature, numerous treatment options have been reported, but consensus about the management of ITW is still missing. The aim of the current study was to evaluate conservative treatment with pyramidal insoles. A total of 193 patients underwent conservative treatment between January 2010 and June 2013. Mean age at the beginning of the treatment was 7.75 ± 0.23 years (range 2.0-17.0 years). For all patients, demographic data, comorbid diseases, passive range of motion (ROM), persistent toe walking, and performed operations were retrospectively evaluated. Following operative treatment was defined failure. Eight (4.15%) patients underwent Achilles tendon lengthening operation after mean therapy time of 2.72 years (range 0.1-7.0 years), 174 cases were treated successfully (90.16%). In 50 cases, toe walking suspended completely after mean therapy time of 2.83 years. In cases of failure, patients were older at diagnosis and at the beginning of the treatment. Mean passive ROM increased over the time. In cases of failure, ROM decreased from the first to the second examination. Conservative treatment of ITW using pyramidal insoles can be effective. Ankle dorsiflexion significantly improved in the patients who were successfully treated. Therapy should start early. A decrease of ROM under therapy should lead to critical revisal of individual therapy. Levels of Evidence: Therapeutic, level IV: Case series